A Pragmatic Situational and Symbiotic Market Requirements Appraisal: An Insight into Textile and Apparel Trade in Africa. (August 2014) - Kariuki, Ndwiga Duncan; Wu, Xiong-Ying; Chen, Li-Hong; Ding, Xue-Mei
African textile and clothing industry though has been in a state of instability, have undergone great transformation to fit in the international trade through implementing the World Trade Organization requirements of a liberalized market and promoting bilateral trade. However, little is known about the current market situation and regulation requirements being implemented. This article provides a comprehensive appraisal to enable understand the African business environment in ways useful in developing this sector, and guiding textile and clothing companies wishing to invest and trade in Africa. It focuses on the structure and characteristics of African four most active Regional Economic Communities (REC) pillars, consisting 42 of the 48 Sub-Saharan Africa (SSA) countries. Through a situational comparative and symbiotic trade analysis of these integrated regional economic markets, this study assesses the current policies towards promoting internal and external trade. The analysis reveals that the integration of regional economic trading blocs has led to the development of more competitive and sustainable markets, and mitigating effects of trade liberalization.